2022
DOI: 10.1109/tte.2021.3133316
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Disturbance Cooperative Fuzzy Tracking Control of Multi-PMSMs Low-Speed Urban Rail Traction Systems

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…The effectiveness of the proposed fixed-time sliding mode observer-based multi-faults estimation method is verified by a PMSM synchronization system described in the work by Dai et al (2022). Considering the actuator faults and sensor faults, the PMSM dynamic model is established.…”
Section: Application To Pmsm Synchronization Systemsmentioning
confidence: 95%
See 3 more Smart Citations
“…The effectiveness of the proposed fixed-time sliding mode observer-based multi-faults estimation method is verified by a PMSM synchronization system described in the work by Dai et al (2022). Considering the actuator faults and sensor faults, the PMSM dynamic model is established.…”
Section: Application To Pmsm Synchronization Systemsmentioning
confidence: 95%
“…The proposed fixed-time multi-faults estimation method is applied to the PMSM synchronization system described in the work by Dai et al (2022), and the system topology is shown in Figure 2. In the work by Dai et al (2022), the control objective of the system is to ensure that the angular velocities of all PMSMs are consistent under external disturbances. On the basis of the work by Dai et al (2022), the actuator faults and sensor faults of the PMSM synchronization system are considered in this paper, and the faults are unevenly distributed among four PMSMs to test the effectiveness of the proposed fixed-time multi-faults estimation method.…”
Section: System Description and Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…PMLSM is a nonlinear, strongly coupled, multivariable system with high requirements for inverters and control algorithms. The traditional AC-DC-AC inverters and control methods can no longer meet the criteria (Dai, Zhang, Xu, Chen, & Yan, 2021).…”
Section: Introductionmentioning
confidence: 99%